018 Clinician prediction of cardiac arrhythmia in patients presenting to the ED with palpitation or pre-syncope. Issue 12 (21st November 2019) - Reed, Matt; Grubb, Neil; Lang, Chris; O'Brien, Rachel; Simpson, Kirsty; Padarenga, Mia; Grant, Alison; Tuck, Sharon; Keating, Liza; Coffey, Frank; Jones, Lucy; Harris, Tim; et al.
Abstract : The IPED study showed that use of a smartphone-based event recorder in ED patients presenting with palpitation or pre-syncope, increased the number of patients in whom an ECG was captured during symptoms over five-fold to more than 55% at 90 days (Reed MJ et al . Lancet eClinical Medicine 2019; 8: 37–46). This pre-planned analysis looked at the ability of ED clinicians to predict cardiac arrhythmia in patients presenting to the ED with palpitation or pre-syncope. Pre-planned sub study analysis of a randomised controlled multi-centre trial. Participants ≥16 years old presenting to 10 UK hospital EDs with palpitation or pre-syncope whose underlying ECG rhythm during these episodes remained undiagnosed after ED assessmentwere enrolled. The treating ED clinician was asked to rate the likelihood of underlying cardiac arrhythmia ranging from 1 (least likely) to 10 (most likely). Participants were then randomised to either an intervention group using a smartphone-based event recorder or a standard care control group. Primary endpoint of this sub study was symptomatic cardiac arrhythmia at 90 days. 243 patients were enrolled. 6 patients had no ED clinician likelihood rating recorded and two further patients were lost to follow-up leaving 235 available for analysis. There were 12 patients recording a symptomatic cardiac arrhythmia at 90 days. These were atrial fibrillation (8), SVT (3), sinus bradycardia (<40 bpm; 1) and atrial flutter (1). One patient recorded 2 categories of arrhythmia. The AUC for prediction of cardiac arrhythmia was 0.81 (95% CI; 0.71–0.90). An ED clinician likelihood rating of 5 or more had 92% sensitivity and 59% specificity for predicting cardiac arrhythmia. Conclusion: ED clinicians are able to predict the liklihood of cardiac arrhythmia in patients presenting to the ED with palpitation or pre-syncope with reasonable accuracy.